2022
DOI: 10.1111/jan.15153
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative exploration of nurses' experiences of the COVID‐19 pandemic using the Reconceptualized Uncertainty in Illness Theory: An interpretive descriptive study

Abstract: Aims:To explore nurses' personal, social and professional experiences in COVID-19 emergency departments and intensive care units based on the Reconceptualized Uncertainty in Illness Theory.Design: This study used an interpretive qualitative descriptive design. Methods:Open-ended interviews were conducted between August and November 2020 with 21 nurses using interview questions based on the Reconceptualized Uncertainty in Illness Theory. Data were analysed using steps informed by hermeneutic phenomenology and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 30 publications
0
1
0
1
Order By: Relevance
“…The pandemic has had deleterious effects on nursing staff and been associated with uncertainty (Turgut et al, 2022 ), fear and emotional exhaustion (Sarabia‐Cobo et al, 2021 ), psychological distress (Hamama et al, 2021 ) and burnout (Galanis et al, 2021 ; Manzano García & Ayala Calvo, 2021 ) in nurses. We have gained insights into the moral distress experienced by hospital nurses during the pandemic, and know that the causes of the distress were varied and included issues with availability of personal protective equipment (PPE), concerns about transmission of infection from work to home and providing care to patients dying alone (Foli et al, 2021 ; Lake et al, 2022 ; McCallum et al, 2021 ).…”
mentioning
confidence: 99%
“…The pandemic has had deleterious effects on nursing staff and been associated with uncertainty (Turgut et al, 2022 ), fear and emotional exhaustion (Sarabia‐Cobo et al, 2021 ), psychological distress (Hamama et al, 2021 ) and burnout (Galanis et al, 2021 ; Manzano García & Ayala Calvo, 2021 ) in nurses. We have gained insights into the moral distress experienced by hospital nurses during the pandemic, and know that the causes of the distress were varied and included issues with availability of personal protective equipment (PPE), concerns about transmission of infection from work to home and providing care to patients dying alone (Foli et al, 2021 ; Lake et al, 2022 ; McCallum et al, 2021 ).…”
mentioning
confidence: 99%
“…A qualitative study with 21 nurses who worked in the emergency or intensive care unit of a hospital in Turkey during the pandemic showed that despite experiencing multiple sources of uncertainty, these professionals focused on patient care and satisfaction as a way to manage uncertainty and give meaning to their experience, recognizing their personal and professional growth throughout the process ( 14 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Sobre este aspecto, um estudo qualitativo com 21 enfermeiros que trabalharam na unidade de emergência ou terapia intensiva em um hospital da Turquia durante a pandemia evidenciou que, apesar das múltiplas fontes de incerteza vivenciadas pelos participantes, estes profissionais procuraram focar no cuidado ao paciente e na satisfação como forma de gerenciar a incerteza e conferir sentido à sua experiência, reconhecendo inclusive seu crescimento pessoal e profissional durante todo o processo ( 14 ) .…”
Section: Discussionunclassified
“…Yapı sağlayıcılar ise yaşanılan belirsizliği olumlu ya da olumsuz etkileyebilen, sağlık profesyonelleri, aile ve arkadaş gibi sosyal çevreler olarak belirtilmektedir. 13,14 BELiRSizLiğiN DEğERLENDiRiLMESi…”
Section: Belirsizliğin öNcüleriunclassified